High-crystallinity g-C3N4 nanosheet photocatalytic material as well as preparation method and application thereof
Through the sodium oxylonate regulation method, the problem of uneven reaction of g-C3N4 during high-temperature calcination was solved, and high crystallinity g-C3N4 nanosheets were prepared, which significantly improved its photocatalytic activity and hydrogen production performance.
Patent Information
- Application Number
- CN202411974508.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, the reaction is uneven during the high-temperature calcination of graphite phase carbon nitride (g-C3N4), resulting in the disordered amorphous or semi-crystalline structure of g-C3N4, which has many defects, limiting its photocatalytic activity.
Sodium oxylonate is used to regulate the crystallinity of g-C3N4, dissolve the dicyanodimide by heating in a water bath, add sodium oxylonate to form a mixed solution, and calcinate after freeze-drying to obtain g-C3N4 containing sodium salt. Then the sodium salt is removed by hydrothermal reaction to obtain g-C3N4 nanosheets with high crystallinity.
The preparation of g-C3N4 nanosheets with high crystallinity was achieved, which reduced internal defects, improved specific surface area and photocatalytic hydrogen production performance, and the production capacity of catalytic cracking water hydrogen production reached 600μmol/g/h.
Smart Images

Figure CN119680610A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano-photocatalytic materials, and specifically relates to a highly crystalline g-C3N4 nanosheet photocatalytic material, a preparation method thereof, and an application thereof. Background Art
[0002] Graphitic carbon nitride (g-C3N4), a polymer semiconductor with a typical two-dimensional layered structure and a narrow bandgap, exhibits excellent visible light absorption, stable physicochemical properties, and good photocatalytic activity. Existing methods for preparing g-C3N4 primarily include solid-state reaction, electrochemical deposition, solvothermal, and thermal polycondensation. The thermal polycondensation method involves calcining a nitrogen-rich organic small molecule precursor at high temperature to induce polycondensation to form a g-C3N4 polymer. However, this method suffers from uneven and disordered reactions during the high-temperature calcination process, resulting in a disordered amorphous or semicrystalline structure in the bulk of the g-C3N4 prepared. The presence of numerous defects in the bulk and surface contributes to low electrical conductivity, limiting the separation of photoexcited charges and resulting in a high electron-hole pair recombination rate, significantly reducing its catalytic activity. Therefore, increasing the crystallinity of g-C3N4 is a key approach to improving its photocatalytic activity.
[0003] Currently, the common methods for preparing crystallized g-C3N4 mainly include high-pressure method, microwave-assisted method, molten salt-assisted method and other methods. Among them, the high-pressure method and microwave-assisted method have too high requirements on equipment and are not suitable for large-scale mass production. The molten salt-assisted method is considered to be a simple and efficient method for synthesizing crystallized g-C3N4, but the types of molten salts that can be used are limited, and the most commonly used LiCl is a toxic substance and needs to be operated in a glove box. Therefore, it is necessary to develop a simple, green and efficient method to synthesize highly crystalline g-C3N4 photocatalytic materials. Summary of the Invention
[0004] To address these challenges, the present invention provides a highly crystalline g-C₃N₄ nanosheet photocatalytic material and a method for preparing the same. This highly crystalline g-C₃N₄ nanosheet photocatalytic material not only possesses a highly crystalline lattice and an ultrathin nanosheet structure, but also exhibits excellent photocatalytic performance. Furthermore, its preparation method is simple, environmentally friendly, and requires minimal equipment, making it suitable for mass production.
[0005] Specifically, in order to achieve the above objectives, the present invention adopts the following technical solutions: A method for preparing a highly crystalline g-C3N4 nanosheet photocatalytic material comprises the following steps: S1, dicyandiamide is scattered in water, and heating in water bath dissolves it to obtain dicyandiamide solution; In described dicyandiamide solution, sodium oxalate is added, mix, and obtain mixed solution A; In described mixed solution A, the concentration of sodium oxalate is 0.0001~0.1g / mL, and the concentration of dicyandiamide is 0.05g / mL; S2, the mixed solution A is freeze-dried to obtain a white powder B uniformly mixed with dicyandiamide and sodium oxalate; S3, calcining the white powder B to obtain a yellow solid g-C3N4 containing sodium salt; S4. Grind the yellow solid g-C3N4 containing sodium salt into a uniform powder, and disperse it in water at room temperature to form a suspension C; subject the suspension C to a hydrothermal reaction, and then filter, wash, and dry to obtain a highly crystalline g-C3N4 nanosheet photocatalytic material.
[0006] In a preferred embodiment, the concentration of sodium oxalate in the mixed solution A is 0.0005-0.01 g / mL.
[0007] In a preferred embodiment, the temperature of the water bath heating in step S1 is 30-80°C.
[0008] In a further preferred embodiment, the water bath heating temperature in step S1 is 30-60°C.
[0009] In a preferred embodiment, the freeze-drying temperature in step S2 is -40°C to -80°C, and the time is ≥48 hours.
[0010] In a further preferred embodiment, the freeze-drying temperature in step S2 is -60°C and the time is 48 hours.
[0011] In a preferred embodiment, the calcination temperature in step S3 is 400°C to 850°C.
[0012] In a further preferred embodiment, the calcination temperature in step S3 is 500°C to 600°C.
[0013] In a preferred embodiment, the calcination time in step S3 is 0.5 h to 6 h.
[0014] In a further preferred embodiment, the calcination time in step S3 is 3 to 5 hours.
[0015] In a preferred embodiment, the temperature of the hydrothermal reaction in step S4 is 180° C. and the time is 1 to 3 hours.
[0016] In a further preferred embodiment, the temperature of the hydrothermal reaction in step S4 is 180° C., and the time is 1 to 2 hours.
[0017] The present invention also provides a highly crystalline g-C3N4 nanosheet photocatalytic material prepared according to any of the above schemes. The highly crystalline g-C3N4 nanosheet photocatalytic material can produce hydrogen by catalytically splitting water under visible light with a production capacity of up to 600 μmol / g / h.
[0018] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: (1) In the present invention, sodium oxalate is used to regulate the crystallinity of g-C3N4. First, sodium oxalate is added to an aqueous solution of dicyandiamide. The resulting mixture is then freeze-dried to remove moisture to obtain a powder of dicyandiamide and sodium oxalate uniformly mixed. The powder is then calcined at a high temperature to obtain a sodium salt-containing g-C3N4 solid. Finally, the sodium salt in the sodium salt-containing g-C3N4 solid is removed by a hydrothermal reaction to obtain g-C3N4 nanosheets with high crystallinity. During the calcination process of this method, the gas generated by the decomposition of sodium oxalate forms a hot air flow, which can effectively prevent the internal structure of g-C3N4 from serious agglomeration, thereby forming a thinner nanosheet structure. Therefore, under the control of sodium oxalate, dicyandiamide can be calcined at a high temperature in the same manner as the traditional preparation of bulk g-C3N4 to form a highly crystalline g-C3N4 nanosheet photocatalytic material. The obtained highly crystalline g-C3N4 nanosheets have few internal defects and a large specific surface area, which can effectively reduce the recombination of photogenerated carriers, thereby effectively improving their photocatalytic hydrogen production performance.
[0019] (2) In the present invention, highly crystalline g-C3N4 nanosheet photocatalytic materials are synthesized by a one-step calcination method. The process is simple, efficient, and environmentally friendly. It has low equipment requirements and does not require expensive synthesis equipment and high-temperature and high-pressure reaction equipment. It is suitable for the large-scale preparation of highly crystalline g-C3N4 nanosheets. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD patterns of conventional bulk g-C3N4 and g-C3N4 nanosheets prepared in Example 1; Figure 2 TEM images of conventional bulk g-C3N4 and g-C3N4 nanosheets prepared in Example 1; Figure 3 N2 adsorption-desorption isotherms of conventional bulk g-C3N4 and g-C3N4 nanosheets prepared in Example 1; Figure 4 UV-vis spectra and Taucplot graphs of conventional bulk g-C3N4 and g-C3N4 nanosheets prepared in Example 1; Figure 5 The photocurrent response curve and electrochemical impedance change curve of the traditional bulk g-C3N4 and the g-C3N4 nanosheets prepared in Example 1; Figure 6 Performance diagram of traditional bulk g-C3N4 and g-C3N4 nanosheets prepared in Example 1 as photocatalysts for hydrogen production. DETAILED DESCRIPTION
[0021] The following content clearly and completely describes the technical solution of the present application in conjunction with the embodiments so that those skilled in the art can fully understand the present application. Obviously, the embodiments described are only some preferred embodiments of the present application, rather than all embodiments. Any equivalent transformation or substitution made by those of ordinary skill in the art to the following embodiments without creative work falls within the scope of protection of the present application.
[0022] In the following examples, the method for evaluating the catalytic hydrogen production performance of bulk g-C3N4 prepared by conventional methods and highly crystalline g-C3N4 nanosheets prepared in this application is as follows: First, 50 mg of sample (bulk g-C3N4 or highly crystalline g-C3N4 nanosheet photocatalytic material) was placed in a 100 mL three-necked flask. 80 mL of a 10% (volume percentage) lactic acid aqueous solution and 134 μL of a 1g / 100 mL chloroplatinic acid aqueous solution (H2PtCl6) were then added to the three-necked flask. To ensure that the photocatalytic hydrogen production reaction was carried out in an oxygen-free environment, nitrogen was purged from the reaction system for 20 minutes to completely remove the air and dissolved oxygen in the water. The flask was then sealed and illuminated with four 420 nm LED lamps (the distance between the light source and the three-necked flask reaction vessel was 1 cm), with an average light intensity of 50 mW / cm 2 . During the irradiation process, stirring was continued to ensure that the photocatalyst powder could be evenly dispersed in the solution. Every 30 minutes of irradiation, 400 μL of gas in the three-necked flask reaction vessel was extracted using a 1000 μL microinjector and then immediately injected into a gas chromatograph (GC-2014C, TCD detector, Shimadzu, Japan) to detect the hydrogen content. Among them, the traditional method for preparing bulk g-C3N4 is as follows: first, dicyandiamide (2.0 g) powder was weighed and placed in a crucible with a volume of 25 mL, and the crucible lid was closed. The crucible was placed in a muffle furnace, heated to 550 ° C, and kept warm for 4 hours. The large yellow block obtained after calcination was ground into fine powder for use, which is the bulk g-C3N4.
[0023] The structural characterization method of the highly crystalline g-C3N4 nanosheet photocatalytic material is as follows: The crystal configuration and crystallinity of g-C3N4 were analyzed using an X-Pert PRO MPD X-ray diffractometer produced by a Japanese company, with a copper target as the radiation source (l = 0.154 nm) and a scanning rate of 5 o / min, with an accelerating voltage of 30 kV and an applied current of 300 mA. The morphology and structure of the samples were characterized by transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM). A JEM-2100F transmission electron microscope was used for both TEM and HRTEM. UV-visible (UV-Vis) absorption spectra of the samples were measured using a Shimadzu UV-2450 UV-Vis spectrophotometer. Al₂O₃ was used as the standard sample, and the wavelength range was 200–800 nm. The photoelectrochemical properties of the samples were analyzed using a Shanghai Chenhua CHI660E electrochemical workstation. The three-electrode system consisted of a FTO glass plate loaded with the synthesized sample as the working electrode, a Pt electrode as the counter electrode, and an Ag / AgCl reference electrode. A 0.5 mol / L Na₂SO₄ solution was used as the electrolyte. The specific surface area of the material was determined using an ASAP 2020 HD88 N2 adsorption-desorption specific surface area analyzer.
[0024] Example 1 A method for preparing a highly crystalline g-C3N4 nanosheet photocatalytic material comprises the following steps: S1. Disperse 2.0 g of dicyandiamide (DCDA) in 40 mL of deionized water and completely dissolve it in a 30°C water bath to obtain a DCDA solution. While stirring, add 0.1 g of sodium oxalate (NaC2O4) powder to the DCDA solution to form a uniform mixed solution A. The concentration of sodium oxalate in this mixed solution A is 0.0025 g / mL, and the concentration of DCDA is 0.05 g / mL.
[0025] S2. Freeze-dry the mixed solution A at -60°C and 0.1 MPa for 48 h to completely remove moisture, thereby obtaining a white powder B which is a uniform mixture of dicyandiamide and sodium oxalate.
[0026] S3. Place the white powder B in a muffle furnace and calcine at 550°C for 4 hours to obtain a yellow solid g-C3N4 containing sodium salt.
[0027] S4. Grind the yellow solid g-C3N4 containing sodium salt into a uniform powder and disperse it in 70 mL of deionized water at room temperature with stirring to form a suspension C. Transfer the suspension C to a hydrothermal reactor, heat it at 180°C for 1 h, and then filter it. Wash the solid with deionized water and dry it to obtain g-C3N4 nanosheets.
[0028] Figure 1Curve a in the figure is the XRD pattern of the bulk g-C3N4 prepared in the conventional method, and curve b is the XRD pattern of the g-C3N4 nanosheets prepared in step S4 of this embodiment. It can be seen from the patterns that both the bulk g-C3N4 and the g-C3N4 nanosheets exhibit the characteristic diffraction peaks of g-C3N4 (13.1 o and 27.4 o This indicates that the sodium oxalate manipulation method did not destroy the intrinsic structure of g-C3N4. In addition, compared with the bulk phase g-C3N4, the (002) crystal plane diffraction peak of g-C3N4 nanosheets shifted significantly, and the peak intensity increased significantly, indicating that the sodium oxalate manipulation method can effectively reduce the disorder of the internal structural unit arrangement of g-C3N4 and improve the crystallinity of the formed g-C3N4.
[0029] Figure 2 Figure A is a TEM image of the bulk g-C3N4 prepared by the traditional method, Figure B is a TEM image of the g-C3N4 nanosheets prepared in step S4 of this example, Figure C is an HRTEM image, and Figure D is an HRTEM image. As can be seen from the figure, the bulk g-C3N4 prepared by the traditional high-temperature calcination method exhibits a large aggregated block structure, while after the addition of sodium oxalate for regulation, the g-C3N4 nanosheets prepared by one-step high-temperature calcination exhibit a thin sheet structure. In addition, the high-resolution TEM image of the sample (Figure C) shows an orderly and tightly stacked structure and lattice fringes of approximately 0.32nm, proving that the g-C3N4 nanosheets have high crystallinity.
[0030] Figure 3 The black curve (curve a) is the N2 adsorption-desorption isotherm of the bulk g-C3N4 prepared by the conventional method, and the blue curve (curve b) is the N2 adsorption-desorption isotherm of the g-C3N4 nanosheets prepared in step S4 of this embodiment. As can be seen from the figure, the bulk g-C3N4 has a very small specific surface area of about 4.8m 2 / g, while the specific surface area of g-C3N4 nanosheets synthesized by sodium oxalate regulation method was significantly improved, about 28.6m 2 / g, which is nearly 6 times the specific surface area of conventional bulk g-C3N4. This indicates that sodium oxalate can effectively prevent severe agglomeration of the internal structure of g-C3N4, and a thinner nanosheet structure can be obtained after high-temperature calcination.
[0031] Figure 4The black curve (curve a) on Figure A is the UV-vis spectrum of the bulk g-C3N4 prepared in the traditional method, and the blue curve (curve b) on Figure A is the UV-vis spectrum of the g-C3N4 nanosheets prepared in step S4 of this embodiment; the black curve (curve a) on Figure B is the Tauc plot curve of the bulk g-C3N4 prepared in the traditional method, and the blue curve (curve b) on Figure B is the Tauc plot curve of the g-C3N4 nanosheets prepared in step S4 of this embodiment. Figure 4 Figure A in the middle shows a blue shift in the absorption edge of g-C3N4 nanosheets synthesized under sodium oxalate. Tauc plot calculations indicate a band gap of 2.36 eV for g-C3N4 nanosheets, compared to 2.55 eV for bulk g-C3N4 synthesized by conventional high-temperature calcination.
[0032] Figure 5 In Figure A, the black curve (curve a) is the photocurrent response curve of bulk g-C3N4 prepared by the conventional method, and the blue curve (curve c) is the photocurrent response curve of g-C3N4 nanosheets prepared in step S4 of this embodiment. The black curve (curve a) in Figure B is the electrochemical impedance change curve of bulk g-C3N4 prepared by the conventional method, and the blue curve (curve c) in Figure B is the electrochemical impedance change curve of g-C3N4 nanosheets prepared in step S4 of this embodiment. As can be seen from Figure A, compared with CCN0 (i.e., bulk g-C3N4 prepared by the conventional method), the CCN0.1 sample (i.e., g-C3N4 nanosheets prepared by adding 0.1g of sodium oxalate) exhibits a significantly enhanced photocurrent density. This is because the photogenerated carrier separation efficiency in the CCN0.1 sample is higher, resulting in a faster interfacial oxidation reaction of photogenerated holes. In addition, it can be seen from Figure B that the highly crystalline g-C3N4 nanosheets exhibit a smaller semicircle than the bulk g-C3N4, indicating that the photogenerated carrier transport efficiency in the highly crystalline g-C3N4 nanosheets is faster.
[0033] Figure 6The black curve (curve a) shows the amount of hydrogen produced by photocatalytic water decomposition of bulk g-C3N4 prepared by the conventional method under visible light (wavelength λ ≥ 420 nm) as a function of time; the blue curve (curve b) shows the amount of hydrogen produced by g-C3N4 nanosheets prepared in step S4 of this embodiment under visible light (wavelength λ ≥ 420 nm) as a function of time. As can be seen from the figure, the photocatalytic hydrogen production capacity of g-C3N4 nanosheets reaches 600 μmol / g / h, which is significantly higher than the photocatalytic hydrogen production performance of bulk g-C3N4 (216 μmol / g / h). This indicates that the g-C3N4 nanosheets obtained by sodium oxalate control, due to their fewer internal defects and larger specific surface area, can effectively suppress the recombination of photogenerated carriers, thereby significantly improving the photocatalytic hydrogen production activity.
[0034] In summary, in this example, g-C3N4 nanosheets with higher crystallinity and better photocatalytic hydrogen production performance were successfully prepared.
[0035] Example 2 In this example, the effect of the amount of sodium oxalate on the quality of highly crystalline g-C3N4 nanosheets was studied. The method for preparing g-C3N4 nanosheets was basically the same as that in Example 1, except that the concentrations of sodium oxalate in the mixed solution A in step S1 were 0 g / mL, 0.00125 g / mL, 0.0025 g / mL, 0.005 g / mL, and 0.0075 g / mL, respectively.
[0036] Experimental results show that when the amount of sodium oxalate added is less than 0.05g, the crystallinity of g-C3N4 is essentially ineffective, resulting in little improvement in the water splitting hydrogen production performance of the prepared photocatalyst compared to that without the addition of sodium salt. However, increasing the amount of sodium oxalate to 5% by mass (relative to the mass of dicyandiamide) accelerates the polycondensation of dicyandiamide to form g-C3N4 through denitrification, reducing the disorder of the internal structural units of g-C3N4 and improving the crystallinity of g-C3N4. Furthermore, the gases produced by the decomposition of sodium oxalate form a hot gas flow, which effectively prevents severe agglomeration of the g-C3N4 internal structure, thereby forming a thinner nanosheet structure and ultimately generating a highly crystalline g-C3N4 nanosheet photocatalyst, thereby improving its photocatalytic hydrogen production performance. When the mass fraction of sodium oxalate added exceeds 5%, the sodium salt produced by the decomposition of molten sodium oxalate can accelerate the denitrification condensation reaction of the precursor, thereby generating more gaseous products, and the yield of the resulting highly crystalline g-C3N4 nanosheets gradually decreases. Therefore, in the preparation process of highly crystalline g-C3N4 nanosheet photocatalytic materials, the optimal amount of sodium oxalate added is 2.5%-5% by mass.
[0037] Example 3 In this example, the effect of water bath temperature on the quality of highly crystalline g-C3N4 nanosheets was studied. The method for preparing g-C3N4 nanosheets was basically the same as that in Example 1, except that the water bath temperatures in step S1 were 20°C, 30°C, 60°C, and 80°C, respectively.
[0038] The experimental results show that when the water bath temperature is 20 o C, dicyandiamide cannot be completely dissolved, so it cannot be evenly mixed with sodium oxalate. When the water bath temperature exceeds 80 o C, dicyandiamide will slowly decompose to produce ammonia. Therefore, in the preparation process of highly crystalline g-C3N4 nanosheet photocatalyst, the preferred water bath temperature is 30~80℃, and the optimal water bath temperature is 30-60℃.
[0039] Example 4 In this example, the effect of freeze-drying time on the quality of highly crystalline g-C3N4 nanosheets was studied. The method for preparing g-C3N4 nanosheets was basically the same as that in Example 1, except that the freeze-drying time in step S2 was 12h, 24h, 48h, and 72h, respectively.
[0040] Experimental results showed that when freeze-drying for 12 hours, due to the high water content in Mixture A, the freeze-drying time was too short and the water could not be completely removed, affecting the properties of the subsequently calcined sample. However, a vacuum freeze-drying time of 48 hours was sufficient to completely sublime the water, resulting in a completely dry dicyandiamide / sodium oxalate precursor suitable for calcination to prepare highly crystalline g-C3N4 nanosheet photocatalysts. While a longer vacuum freeze-drying time could also yield a completely dry precursor, it was more time-consuming. Therefore, 48 hours is the optimal drying time for the preparation of highly crystalline g-C3N4 nanosheet photocatalysts.
[0041] Example 5 In this example, the effect of calcination temperature on the quality of highly crystalline g-C3N4 nanosheets was studied. The method for preparing g-C3N4 nanosheets was basically the same as that in Example 1, except that the calcination temperatures in step S3 were 250°C, 400°C, 550°C, and 850°C, respectively.
[0042] The experimental results show that when the calcination temperature is 250 o C, since dicyandiamide cannot be effectively converted into g-C3N4, high crystalline g-C3N4 nanosheets cannot be obtained. oC, dicyandiamide can be successfully converted into g-C3N4. At the same time, the higher heat treatment temperature can not only promote the denitrification condensation reaction of dicyandiamide and thus accelerate its polymerization, but also introduce cyano groups on the surface of g-C3N4, which significantly improves its photocatalytic performance. Its photocatalytic hydrogen production performance can reach 2.75 times that of bulk g-C3N4. When the temperature is 850 o C, due to the limited thermal stability of g-C3N4, it is easy to decompose into small organic molecules and lose. Therefore, in the preparation process of high-crystalline g-C3N4 nanosheet photocatalytic materials, the preferred calcination temperature is 400℃~850℃, the further preferred temperature is 500~600℃, and the optimal calcination temperature is 550℃. o C.
[0043] Example 6 In this example, the effect of calcination time on the quality of highly crystalline g-C3N4 nanosheets was studied. The method for preparing g-C3N4 nanosheets was basically the same as that in Example 1, except that the calcination time in step S3 was 0.5h, 3h, 4h, and 6h, respectively.
[0044] Experimental results show that when the calcination time is 0.5 h, dicyandiamide is not completely converted to g-C3N4, and the resulting g-C3N4 photocatalytic material still contains unconverted dicyandiamide, resulting in a significant decrease in photocatalytic performance. When the calcination time is 3-5 h, dicyandiamide is successfully converted to g-C3N4, resulting in a highly crystalline g-C3N4 nanosheet photocatalytic material with a hydrogen production rate of up to 600 μmol / g / h. When the calcination time exceeds 5 h, the hydrogen production performance of the prepared highly crystalline g-C3N4 photocatalytic material gradually decreases compared to the sample calcined for 4 h. This is likely due to the destruction of the g-C3N4 structure caused by excessive calcination time, resulting in quality loss. Therefore, in the preparation of highly crystalline g-C3N4 nanosheet photocatalytic materials, the preferred calcination time is 0.5-6 h, with a further preferred time of 3-5 h and an optimal calcination time of 4 h.
[0045] Example 7 In this example, the effect of the hydrothermal reaction time on the quality of highly crystalline g-C3N4 nanosheets was studied. The method for preparing g-C3N4 nanosheets was basically the same as that in Example 1, except that the heating time of the hydrothermal reaction in step S4 was 0.5h, 1h, 2h, 3h, and 3.5h, respectively.
[0046] The experimental results show that when the hydrothermal reaction time is 0.5h, the short hydrothermal treatment cannot completely remove the Na2CO3 embedded in g-C3N4. When the hydrothermal reaction time is 1h, not only can the water-soluble Na2CO3 be removed, but the relatively short hydrothermal treatment will not significantly damage the structure of g-C3N4, thereby significantly improving its photocatalytic performance. When the hydrothermal reaction time is 3.5h, the holding time is too long and the structure of g-C3N4 will be changed. Therefore, the hydrothermal reaction time is preferably 1~3h, more preferably 1~2h, and the optimal hydrothermal reaction time is 1h.
[0047] The embodiments described above are merely preferred embodiments of the present application and are not intended to limit the scope of protection of the present application. For anyone skilled in the art, the present application may have various modifications and variations. Any simple equivalent changes and modifications made based on the scope of protection of the present application and the contents of the specification should be included in the scope of protection of the present application.
Claims
1. A method for preparing a highly crystalline g-C3N4 nanosheet photocatalytic material, characterized in that: The following steps are involved: S1, dicyandiamide is dispersed in water, and heating in a water bath dissolves it to obtain a dicyandiamide solution; sodium oxalate is added to the dicyandiamide solution, and mixed to obtain a mixed solution A; the concentration of sodium oxalate in the mixed solution A is 0.0001 ~ 0.1g / mL, and the concentration of dicyandiamide is 0.05g / mL; S2, freeze-drying the mixed solution A to obtain a white powder B uniformly mixed with dicyandiamide and sodium oxalate; S3, calcining the white powder B to obtain a yellow solid g-C3N4 containing sodium salt; S4. Grind the yellow solid g-C3N4 containing sodium salt into uniform powder, and disperse it in water at room temperature to form a suspension C; subject the suspension C to a hydrothermal reaction, and then filter, wash, and dry to obtain a highly crystalline g-C3N4 nanosheet photocatalytic material.
2. The preparation method according to claim 1, characterized in that: The concentration of sodium oxalate in the mixed solution A is 0.0005-0.01 g / mL.
3. The preparation method according to claim 1, characterized in that: The temperature of water bath heating in step S1 is 30-80° C.; or / and the temperature of freeze drying in step S2 is -40° C.-80° C., and the time is ≥48 hours.
4. The preparation method according to claim 3, characterized in that: The temperature of water bath heating in step S1 is 30-60° C.; or / and the temperature of freeze drying in step S2 is -60° C. and the time is 48 hours.
5. The preparation method according to claim 1, characterized in that: The calcination temperature in step S3 is 400° C. to 850° C.; or / and the calcination time is 0.5 h to 6 h.
6. The preparation method according to claim 5, characterized in that: The calcination temperature in step S3 is 500° C. to 600° C.; or / and the calcination time is 3 to 5 hours.
7. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step S4 is 180° C. and the time is 1 to 3 hours.
8. The highly crystalline g-C3N4 nanosheet photocatalytic material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the highly crystalline g-C3N4 nanosheet photocatalytic material according to claim 8 as a photocatalytic material under visible light.
10. The use according to claim 9, characterized in that: The highly crystalline g-C3N4 nanosheet photocatalytic material is used to catalytically decompose water to produce hydrogen under visible light.
Citation Information
Cited By
Sodium sulfate / crystallized carbon nitride composite material and preparation and application thereof
CN122321928A